Causes Of Deaths Among Children Below Five Years Using Verbal Autopsy Tool in Dehradun, India - Sushil Dalal; Devidas T Khedkar; Jitendra S Bhawalkar (Medsci Publications, 2016)
Background: In India about 2.1 million child deaths occur every year. However causes of deaths remain uncertain as many deaths occur outside health system. The study was conducted to find out causes of deaths using verbal autopsyin Dehradun. Methodology: The survey was done on all the house of the deceased children residing in our field practice areas by visiting their houses. Results: there were 83 deaths reported during study period which shows that five most common causes of deaths in children were pneumonia, milk aspiration, and birth asphyxia. Conclusion: Most of the under five children deaths can be prevented by regular and effective training programmes for health care providers and pregnant females whereas early recognition of danger signs and early referral system can save many precious lives.